2021
DOI: 10.1016/j.jpsychires.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mental illness and social stress in hospital workers treating COVID-19: Paradoxical distress during pandemic era

Abstract: Background The coronavirus disease 2019 (COVID-19) has affected all countries in the world. Hospital workers are at high risk of mental illness, such as anxiety and depression. Furthermore, they also face many social stresses, such as deterioration of human relations and income reduction. Apart from mental illness, these social stresses can reduce motivation and lead to voluntary absenteeism, which contribute to a collapse of medical systems. Thus, for maintaining medical systems, it is crucial to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“… Sun et al, 2021 ), ( Tsang et al, 2021 ), (H. Wang et al, 2021 ), (Y. Wang et al, 2021 ), ( Wickens et al, 2021 ), ( Wu et al, 2021a ), (R. Yadav et al, 2021 ), ( Yan et al, 2021 ), ( Yasmin et al, 2021 ), ( Young et al, 2021 ) Gender 30 11.86 (Xu Chen et al, 2021 ), ( Chi et al, 2021 ), ( Devkota et al, 2021 ), ( Fang et al, 2021 ), ( Glenister et al, 2021 ), (Huang et al, 2021), ( Rashid et al, 2021 ), ( Kibbey et al, 2020 ), (S. Liu et al, 2021 ), ( Liu et al, 2020 ), ( Matsumoto et al, 2021 ), ( Moore et al, 2021 ), ( Nomura et al, 2021 ), ( Matsumoto et al, 2021 ), ( Moore et al, 2021 ), ( Nomura et al, 2021 ), ( Pandey et al, 2021 ), ( Parthasarathy et al, 2021 ), ( Peng et al, 2021 ), ( Robillard et al, 2021 ), ( Rossell et al, 2021 ), ( Safa et al, 2021 ), ( Sakib et al, 2021 ), ( Song et al, 2020 ), ( Suzuki et al, 2021 ), ( Turna et al, 2021 ), ( Veldhuis et al, 2021 ), (Y. Wang et al, 2021 ), ( Wong et al, 2021 ), ( Wu et al, 2021a ), (R. Yadav et al, 2021 ), ( Yan et al, 2021 ) Deterioration of medical problems/ medical condition/ diagnosed disease/ underlying disease 21 8.30 (J.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Sun et al, 2021 ), ( Tsang et al, 2021 ), (H. Wang et al, 2021 ), (Y. Wang et al, 2021 ), ( Wickens et al, 2021 ), ( Wu et al, 2021a ), (R. Yadav et al, 2021 ), ( Yan et al, 2021 ), ( Yasmin et al, 2021 ), ( Young et al, 2021 ) Gender 30 11.86 (Xu Chen et al, 2021 ), ( Chi et al, 2021 ), ( Devkota et al, 2021 ), ( Fang et al, 2021 ), ( Glenister et al, 2021 ), (Huang et al, 2021), ( Rashid et al, 2021 ), ( Kibbey et al, 2020 ), (S. Liu et al, 2021 ), ( Liu et al, 2020 ), ( Matsumoto et al, 2021 ), ( Moore et al, 2021 ), ( Nomura et al, 2021 ), ( Matsumoto et al, 2021 ), ( Moore et al, 2021 ), ( Nomura et al, 2021 ), ( Pandey et al, 2021 ), ( Parthasarathy et al, 2021 ), ( Peng et al, 2021 ), ( Robillard et al, 2021 ), ( Rossell et al, 2021 ), ( Safa et al, 2021 ), ( Sakib et al, 2021 ), ( Song et al, 2020 ), ( Suzuki et al, 2021 ), ( Turna et al, 2021 ), ( Veldhuis et al, 2021 ), (Y. Wang et al, 2021 ), ( Wong et al, 2021 ), ( Wu et al, 2021a ), (R. Yadav et al, 2021 ), ( Yan et al, 2021 ) Deterioration of medical problems/ medical condition/ diagnosed disease/ underlying disease 21 8.30 (J.…”
Section: Resultsmentioning
confidence: 99%
“… Chen et al, 2021 ), ( Fang et al, 2021 ), ( Fukase et al, 2021 ), ( Gotlib et al, 2021 ), ( Hammond et al, 2021 ), ( Hao et al, 2021 ), ( Hazarika et al, 2021 ), ( Kibbey et al, 2020 ), ( Liu et al, 2020 ), ( Mistry et al, 2021 ), ( Nishimura et al, 2021 ), ( Robillard et al, 2021 ), ( Sakib et al, 2021 ), ( Suzuki et al, 2021 ), ( Tsang et al, 2021 ), (Y. Wang et al, 2021 ), ( Wong et al, 2021 ), ( Yang et al, 2021 ), ( Young et al, 2021 ) Age 20 7.91 ( An et al, 2021 ), ( Cheema et al, 2021 ), ( Fukase et al, 2021 ), ( Glenister et al, 2021 ), ( Kar et al, 2021 ), ( Kar et al, 2021 ), ( Rashid et al, 2021 ), ( Kim et al, 2021 ), ( Matsumoto et al, 2021 ), ( Nkire et al, 2021 ), ( Robillard et al, 2021 ), ( Rossell et al, 2021 ), (Song et al, 2021), ( Tang et al, 2021 ), ( Turna et al, 2021 ), ( Veldhuis et al, 2021 ), ( Wong et al, 2021 ), ( Yan et al, 2021 ), ( Yang et al, 2021 ), ( Yunus et al, 2020 ) Income disruption/ financial restraints 19 7.51 (Xi an Chen et al, 2021 ), ( Cheng et al, 2021 ), ( Devkota et al, 2021 ), ( Fukase et al, 2021 ), ( ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, Matsumoto, et al conducted a mental health assessment of 588 HCPs on working days in order to study exposure to the coronavirus, anxiety, and depression. 19) They found that 47 (8.0%) reported severe anxiety and 40 (6.8%) reported severe depressive symptoms, with older age and female sex being common risk factors. More recently, a questionnaire conducted by Yamano, et al on 1032 children in the COVID-19 era showed that the risk of stress among the children of HCPs was twice as high as that of nonhealthcare professionals' children.…”
Section: Issues Encountered By Physicians During the Covid-19 Pandemicmentioning
confidence: 97%